Proportion and factors affecting for post-natal care utilization in developing countries: A systematic review - Adhikari, Chiranjivi; Yadav, Rajesh Kumar; Timilshina, Purnima; Ojha, Renuka; Gaire, Deepika; Ghimire, Ashmita (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Background: Majority of neonatal and maternal mortalities occur in developing countries. Moreover, around half of both mortalities occur in immediate postnatal period. Postnatal care utilization is aimed to reduce both mortalities and promote their health status.Methods: We searched PubMed, Google Scholar and HINARI between Jan 1, 2006 and Apr 31, 2014. Cross-sectional studies, surveys published in English language with finding of percentage of and factors affecting postnatal care utilization were included in the analysis. Weighted percentage with 95% CI was calculated to summarize the proportion. Odds ratio of minimum and maximum value was used to summarize associated factors. P-value